2010
DOI: 10.1159/000321734
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Stroke Incidence in Hong Kong Differ by Stroke Subtype

Abstract: Background: The population in Hong Kong is mainly Chinese, but their lifestyle is increasingly westernized. It is uncertain whether the trends of stroke in Hong Kong would follow a Chinese or Western pattern. This is the first study to examine the trends of ischemic and hemorrhagic stroke in Hong Kong between 1999 and 2007 with a view to providing data for planning preventive programs and resources for treatment. Methods: Data from the Clinical Management System database of the Hong Kong Hospital Authority for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 64 publications
2
40
0
1
Order By: Relevance
“…29 Females tend to have lower rates of ischemic stroke, but estimated risk rates have a huge range from 0.7 per 100 000 to 115.3 per 100 000. 27 In the United States, the IRR among males is 1.22 (95% CI, 1.08-1.39) compared with females. 26 In the United States, the incidence of ischemic stroke varies by race.…”
Section: Ischemic Strokementioning
confidence: 99%
“…29 Females tend to have lower rates of ischemic stroke, but estimated risk rates have a huge range from 0.7 per 100 000 to 115.3 per 100 000. 27 In the United States, the IRR among males is 1.22 (95% CI, 1.08-1.39) compared with females. 26 In the United States, the incidence of ischemic stroke varies by race.…”
Section: Ischemic Strokementioning
confidence: 99%
“…Compared with white populations of European origin, Chinese populations have been reported to have a higher incidence of stroke overall, a higher proportion of ICH, and a different distribution of ischemic stroke subtypes. [4][5][6][7][8] However, reliable comparisons have been precluded by a lack of methodologically robust studies of stroke incidence among Chinese populations, age standardization of incidence rates in different studies to different standard populations, and variable methods for classifying stroke types and subtypes. 9,10 Furthermore, no previous review of the epidemiology of stroke in Chinese populations has taken an explicitly systematic approach.…”
mentioning
confidence: 99%
“…18 In China, for instance, it was reported that temporal trends of IS incidence have increased over recent years, 19 whereas trends in Hong Kong Chinese were reported to have decreased. 27 A recent systematic review has confirmed the lack of reliable information regarding temporal trends of stroke in most countries in Southeast Asia, despite the substantial impact these countries have on the global burden from cerebrovascular diseases. 17 Their findings indicate the need for reliable epidemiological data from the region that will help to better describe variable trends across countries of different developmental stage, identify mechanisms that are specific to ethnicity, and develop culturally adequate preventive strategies that could have considerable impact on the future global burden of cerebrovascular diseases.…”
Section: Discussionmentioning
confidence: 99%